(untitled) (Damascus University Journal of arts and humanities sciences, 2026)
The study aimed to measure the rate at which Syrian university students use social media sites in their academic achievement, in addition to identifying the reasons for use and aspects of benefit. The study was carried out on a sample of (175) students between (28/11/2024 to 31/12/2024). The results showed that 75.8% of the study sample members use social media sites in their academic achievement, and that the rate of their use of these sites is high by 46.3%. YouTube is the most used social media site among the respondents, and the degree of utilization of social media sites in academic achievement is high, as it is a means of obtaining previous exam forms, syllabi, and knowing the dates of periodic meetings with teachers. Accordingly, it was highlighted that the higher the rate of using social media sites in academic achievement, the higher the degree of benefit from using them to a low degree, and that there are differences in the rate of use according to the variable of the type of college in favor of students of literary colleges. Moreover, there are statistically significant differences in the degree of benefit from using social media sites in academic achievement in favor of females more than males, and for students who have not yet obtained their university degree compared to postgraduate students.